PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN DI AKASHIRO COFFEE - Haufi Sukmamedian; Dailami; Nensi Lapotulo (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2022)
Purchasing decisions are consumer behaviors based on impulses and motivations that will then generate a sense of meeting needs. The user will have a reason in choosing the goods, then the customer will decide whether to buy the goods or not. For example, consumers have bought product A and are satisfied so that the consumer makes a purchase decision on product A. If consumers have no experience or have never tried a product then consumers tend to trust goods or products that are more familiar and trusted. Consumers tend to make the product brand image into an image before consumers choose and buy products. so the company must be able to attract the attention of consumers and must build a positive brand image in order to attract purchasing decisions. Brand image is the perception and confidence carried out by consumers, as reflected in the association that occurs in the customer impression. The more positive the brand image owned by a company, the higher it is and the more confident it is for consumers to buy the product. This reason is reinforced by research by said that brand image can improve customer decisions in buying products.